IDEOLOGI GADIS PANTAI KARYA PRAMOEDYA ANANTA TOER: SEBUAH KAJIAN HEGEMONI GRAMSCI - Surastina Surastina; Sudarmaji Sudarmaji; Tri Riya Anggraini (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2021)
The purpose of this study is to examine and describe the ideological formations contained in Pramoedya Ananta Toer's Girl Beach by using Gramsci's theory of hegemony. The method used in this study is a qualitative descriptive method. Qualitative descriptive method is used to describe the ideology of the novel Gadis Pantai by Pramoedya Ananta Toer using Gramsci's hegemonic theory of analysis. Based on the results of the analysis conducted on Girl Beach by Pramoedya Ananta Toer, several ideologies were found, namely capitalism, authoritarianism, modernism, humanism, feudalism, and feminism.